MANAJEMEN PENGENDALIAN MUTU DI SEKOLAH DASAR NEGERI SURABAYA BARABALI, LOMBOK TENGAH - Habibi, Muhamad Ridwan (LPPM Institut Pendidikan Nusantara Global, 2020)
Quality in education units is very important as a guarantee and standard of education management. SD Surabaya Barabali Lombok as a state primary school education level is expected to be measured and accountable for its processes and outcomes. The purpose of this study was to find out how the implementation of quality control management at SD Surabaya Barabali, Central Lombok, both in the field of curriculum and student development. The research method is field research at SD Surabaya Barabali, Central Lombok. The results of this study indicate that quality control management has not been implemented, the importance of compiling quality standards at SD Surabaya Barabali Central Lombok, implementation obstacles related to political policies, budgets, resources, and awareness, and quality control must be developed in SD Surabaya Barabali Central Lombok in order to create quality. which is guaranteed.